Lawn people. How grasses, weeds and chemicals make us who we are - Saurí, David (Documents d’Anàlisi Geogràfica, 2009)
ROBBINS, Paul Lawn people. How grasses, weeds and chemicals make us who we are Filadèlfia, PA: Temple University Press. XXI, 2007, 179 p. ISBN: 139781592135783